Workplace‐Based Assessment for Vocational Registration of International Medical Graduates. Issue 4 (October 2014) - Lillis, Steven; Van Dyk, Valencia
<x xml:space="preserve">Abstract</x> Introduction Medical regulatory authorities need efficient and effective methods of ensuring the competence of immigrating international medical graduates (IMGs). Not all IMGs who apply for specialist vocational registration will have directly comparable qualifications to those usually accepted. As general licensure examinations are inappropriate for these doctors, workplace‐based assessment (WBA) techniques would appear to provide a solution. However, there is little published data on such outcomes. Methods All cases of WBA (n = 81) used for vocational registration of IMGs in New Zealand between 2008 and 2013 were collated and analyzed. Results The successful completion rate of IMGs through the pathway was 87%. The majority (64%) undertook the year of supervised practice and the final assessment in a provincial center. For those unsuccessful in the pathway, inadequate clinical knowledge was the most common deficit found, followed by poor clinical reasoning. Discussion A WBA approach for assessing readiness of IMGs for vocational registration is feasible. The constructivist theoretical perspective of WBA has particular advantages in assessing the standard of practice for experienced practitioners working in narrow scopes than traditional methods of assessment. The majority of IMGs undertook both the clinical year and the assessment in provincial hospitals, thus providing a workforce for underserved areas.